Gasification of biomass in a circulating fluidized bed based calcium looping gasifier for hydrogen-enriched gas production: experimental studies. Issue 6 (2nd November 2017) - Acharya, Bishnu; Dutta, Animesh; Basu, Prabir
ABSTRACT: This paper presents experimental studies of circulating fluidized bed based calcium looping gasification (CFB-CLG) system for producing hydrogen-enriched gas from biomass. The merit of this system is that it captures carbon dioxide (CO2 ) during the process using the inexpensive and easily available sorbent calcium oxide (CaO). The process also regenerates the sorbent internally and produces a relatively pure stream of CO2 . A laboratory scale calcium looping gasification system based on a circulating fluidized bed was developed and tested. Experiments conducted to gasify sawdust in the CFB-CLG system shows that it could produce a gas with 81% hydrogen and CO2 as low as 5%. Exergy analysis of the calcium looping system is done and the efficiency is 78.77%.